Peran Modal Intelektual dan Manajemen Pengetahuan dalam Meningkatkan Kinerja Perusahaan FMCG - Maharsyah, Aburizal; Adi , Ignatius Trisna; Utami, Sahwa Putri; Hanoum, Syarifa; Durman, Thedosia Yunita (Li Falah: Journal of Islamic Economics and Business, 2025)
This study aims to analyze the role of Intellectual Capital (IC) and Knowledge Management (KM) in influencing Firm Performance (FP) in companies within the Fast-Moving Consumer Goods (FMCG) sector. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, with data collected through questionnaires distributed to 104 respondents across various job levels. The results indicate that both IC and KM have a positive and significant impact on FP. Furthermore, KM was found to partially mediate the relationship between IC and FP, suggesting that a company's success is not solely determined by the presence of intellectual capital but also by its ability to manage and utilize knowledge effectively. These findings highlight the importance of integrating IC and KM to build a sustainable competitive advantage. This study offers theoretical contributions to the development of IC and KM literature, as well as practical insights for managers in designing knowledge-based strategies to enhance FP of FMCG companies in a highly competitive and dynamic market.